Pengaruh Transaksi Pihak – Pihak Istimewa Terhadap Kinerja Keuangan Perusahaan Properti - Helmi Herawati; Aan Zulyanto; Dimas Gilang Wahyudi (Universitas Malahayati, 2022)
The effect of special party transactions on the financial performance of property companies (Empirical Study on Property Companies on the Indonesia Stock Exchange 2015-2018). This study aims to determine whether sales with special parties affect the financial performance of property companies and whether purchases from special parties affect the financial performance of property companies.The results of the research conducted show that 1. sales transactions to special parties affect the company's financial performance. This shows that the greater the sales transactions made to special parties, the better the financial performance of the property company. 2. Purchase transactions with special parties do not affect the property company's financial performance